The impact of ocean acidification and warming on the skeletal mechanical properties of the sea urchin Paracentrotus lividus from laboratory and field observations. (16th February 2015) - Collard, Marie; Rastrick, Samuel P. S.; Calosi, Piero; Demolder, Yoann; Dille, Jean; Findlay, Helen S.; Hall-Spencer, Jason Michael; Milazzo, Marco; Moulin, Laure; Widdicombe, Steve; Dehairs, Frank; Dubois, Philippe
Abstract: Increased atmospheric CO2 concentration is leading to changes in the carbonate chemistry and the temperature of the ocean. The impact of these processes on marine organisms will depend on their ability to cope with those changes, particularly the maintenance of calcium carbonate structures. Both a laboratory experiment (long-term exposure to decreased pH and increased temperature) and collections of individuals from natural environments characterized by low pH levels (individuals from intertidal pools and around a CO2 seep) were here coupled to comprehensively study the impact of near-future conditions of pH and temperature on the mechanical properties of the skeleton of the euechinoid sea urchin Paracentrotus lividus . To assess skeletal mechanical properties, we characterized the fracture force, Young's modulus, second moment of area, material nanohardness, and specific Young's modulus of sea urchin test plates. None of these parameters were significantly affected by low pH and/or increased temperature in the laboratory experiment and by low pH only in the individuals chronically exposed to lowered pH from the CO2 seeps. In tidal pools, the fracture force was higher and the Young's modulus lower in ambital plates of individuals from the rock pool characterized by the largest pH variations but also a dominance of calcifying algae, which might explain some of the variation. Thus, decreases of pH to levels expected for 2100 did not directly alter the mechanical properties of the test of P. lividus . Since the maintenance of test integrity is a question of survival for sea urchins and since weakened tests would increase the sea urchins' risk of predation, our findings indicate that the decreasing seawater pH and increasing seawater temperature expected for the end of the century should not represent an immediate threat to sea urchins vulnerability.